AB0041 Number of Mast Cell Are Higher in End Stage Knee Osteoarthritis. (10th June 2014) - De Lange-Brokaar, B.; Andersen, S.; Dorjée, A.; Yusuf, E.; Herb-van Toorn, L.; Kroon, H.; Osch, G.; Zuurmond, A.-M.; Stojanovic-Susulic, V.; Nelissen, R.; Toes, R.; Kloppenburg, M.; et al.
Abstract : Background: Mast cells could be important in osteoarthritis (OA), as it is the only type of immune cell whose numbers were shown to be as high or sometimes higher compared to rheumatoid arthritis (RA). To assess their role in OA, we investigated whether the number and activation status of mast cells varies with the disease stage in OA. Objectives: To compare number of mast cells and their degranulation status in synovial tissue between different stages of OA. Methods: 56 patients with symptomatic knee OA attending the rheumatology or orthopaedic outpatient clinic were included. 22 patients with mild to established knee OA (mean (±SD) age 60 (7) yrs, 73% women, median (range) BMI 29 (24-44) kg/mm 2, median (range) 2(1-4) KL grade)) underwent arthroscopy of the knee and synovial biopsies were obtained. 34 patients with end-stage knee OA (mean (±SD) age 63 (9) yrs, 59% women, median (range) BMI 29 (21-50) kg/mm 2, median (range) KL grade 3.0 (1-4)) underwent arthroplasty and synovial tissues were collected. After haematoxylin and eosin staining, samples were microscopically scored on following features: synovial lining layer hyperplasia (0-3), activation of resident cells/stroma (0-3) and inflammatory infiltrates (0-3). Mean total scores (0-9) by 3 observers was used. Synovial tissue biopsies were investigated by double immunofluorescence for both CD117 and tryptase. Number of total mast cells CD117+ and degranulated (CD117+tryptase- or CD117+with visible granules outside cell) and non-degranulated mast cells (CD117+tryptase+ with no granules seen outside cell) were counted in 10 sub sequential high-power fields (HPF) at two locations in synovial tissue by 3 blinded observers. Mean number of mast cells by 3 observers per patient per 10 HPF were used for analysis. Mann-Witney U and Kruskal-Wallis tests were used for comparisons. Results: A mean (±SD) total histology grade of 2.5 (1.6) was observed for all patients. Mast cells were readily observed and were mainly located in the sublining layer. Median (range) of mast cells per patient per 10 HPF was 21 (1-116) and was significantly higher in the end-stage (26 (1-116)) than in the mild to established (12 (1-48)) knee OA (p-value=0.007)) (Fig. 1a ). Furthermore, total number of mast cells significantly increased with increasing KL grade (p-value=0.001). A relatively small proportion of the mast cells was degranulated in both groups (Fig. 1b ). A trend towards a higher percentage of degranulated mast cells in mild to established OA compared to end-stage OA was observed, although it did not reach significance (Fig. 1b) Conclusions: Our data indicate that there is an accumulation of mast cells in end-stage OA compared to mild/established OA. Furthermore a less activated state of mast cells was observed in end-stage OA. This suggests that mast cells might have different biological functions in different phases of the disease. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4290